Fisetin in Cancer: Attributes, Developmental Aspects, and Nanotherapeutics - Rachna M. Kumar; Hitesh Kumar; Tanvi Bhatt; Rupshee Jain; Kanan Panchal; Akash Chaurasiya; Vikas Jain (MDPI AG, 2023)
Cancer is one of the major causes of mortality, globally. Cancerous cells invade normal cells and metastasize to distant sites with the help of the lymphatic system. There are several mechanisms involved in the development and progression of cancer. Several treatment strategies including the use of phytoconstituents have evolved and been practiced for better therapeutic outcomes against cancer. Fisetin is one such naturally derived flavone that offers numerous pharmacological benefits, i.e., antioxidant, anti-inflammatory, antiangiogenic, and anticancer properties. It inhibits the rapid growth, invasiveness, and metastasis of tumors by hindering the multiplication of cancer cells, and prompts apoptosis by avoiding cell division related to actuation of caspase-9 and caspase-8. However, its poor bioavailability associated with its extreme hydrophobicity hampers its clinical utility. The issues related to fisetin delivery can be addressed by adapting to the developmental aspects of nanomedicines, such as formulating it into lipid or polymer-based systems, including nanocochleates and liposomes. This review aims to provide in-depth information regarding fisetin as a potential candidate for anticancer therapy, its properties and various formulation strategies.